Test of the Effectiveness of Biochar and Mineral Fertilizer on The Growth and Yield of Two Broad Bean Vicia Faba L - Qotaiba.Saleh. Sheikh; Abdulsalam Rajab Ahmed Al-Jumaily; Jassim. Mohammed. Aziz (Zien Journals, 2022)
The experiment was applied in two successive winter seasons 2020 and 2021, with the aim of studying the growth and yield of two cultivars of bean, the Turkish variety A1 )Bakla sakiz) and the Spanish A2 variety (Histal), and three levels of NPK mineral fertilizer 20, 20, 20 and the total quantity was 200 kg.ha-1 S1 no addition and S2 adding 50% of the total fertilizer and S3 adding 100%, and three levels of biochar ( corn stalks and poultry manure) H1 no addition and H2 adding 7 tons.ha-1 and H3 adding 14 tons.ha-1 and three replicates using a design. (R.C.B.D). The results of the study showed significant differences between cultivars, fertilizer and biochar and the interaction between them, and for all the studied traits two seasons, The Spanish cultivar was significantly superior to the Turkish cultivar in terms of plant height, leaf area, chlorophyll content in leaves, weight of 100 seeds and total seed yield, except that the number of branches per plant did not differ significantly two seasons, The S3 level was significantly distinguished in all growth traits, weight of 100 seeds two seasons and a recipe for yield for the 2021 season, While the level S2 was significantly superior in the trait of the achievement for the 2020 season, the level H3 was significantly superior in all the characteristics of the study two seasons, The binary interaction between cultivars, manure, cultivars and charcoal was significant, as the two combinations A2S3 and A2H3 excelled in all study characteristics two seasons, The triple interaction between cultivars, fertilizer and charcoal was significant, as the two combinations A2S2H3 and A2S3H3 were superior in plant height, chlorophyll and yield two seasons and 100-seed weight trait for the 2020 season, While the combinations A1S3H2, A1S3H3, A2S3H2 and A2S3H3 were significantly distinguished in the characteristics of number of branches on the plant and leaf area two seasons.
Keywords: Plant Height; Branches; Leaf Area; Grain Yield